Professional self-assessment of the future special teacher (Journal of Educational Sciences, 2023)
The article deals with the problems of professional self-assessment of a future special teacher. Previously,various approaches were investigated in determining the necessary personal and professionalqualities, the content of education and professional training of a teacher. For the personality of the futurespecial teacher today it is necessary to develop such qualities as competence, decency, politeness,self-control of their personal and professional behavior. The analysis of scientific works and empiricalexperience has shown the importance of a holistic study of the professional qualities of a future specialteacher. The purpose of the research is the scientific substantiation of the development of professionalself–esteem of the future special teacher. A structural and meaningful model of the development ofprofessional self-esteem of students-future special teacher was developed. The model includes threecomponents: cognitive, motivational, and self-management. The experiment was attended by 220 studentsAbai KazNPU. To establish the level of self-government and self-esteem, diagnostics were used:I. Motkov’s questionn aire, G.Kazantseva’s questionnaire “Self-assessment of personality”, as well asdiagnostics of Bubnova’s value orientations. The results of the study made it possible to establish anaverage level of self-management and self-development among students of the 2-3 courses, higher thanaverage in the 4th year. The number of students with normal self-esteem by the 4th year increases from46.7% to 64.3%. For the development of self-management and self-esteem of students, a new course“Self-assessment elective course” was tested.Key words: self-assessment, self-improvement, professional, Correctional pedagogy, special education.